Consensus Sequences for Gag and Pol Introduced into HIV-1 Clade B Laboratory Strains Differentially Influence the Impact of Point Mutations Associated with Immune Escape and with Drug Resistance on Viral Replicative Capacity - Sven Breitschwerdt; Benedikt Grandel; Benedikt Asbach; Franziska Winter; Todd Allen; Ralf Wagner; Bernd Salzberger; Arne Schneidewind (Viruses, 2025)
Viral evasion from effective human immunodeficiency virus type 1 (HIV-1)-specific CD8+ T-cell responses and from antiretroviral therapy through viral sequence variation is frequently accompanied by a loss in viral fitness. The impact of sequence variations on replication capacity in vitro was mostly studied by introducing single mutations into a specific clonal strain such as NL4-3. How the specific viral backbone itself impacts replicative fitness remains elusive. To test for a potential effect of the viral backbone, we constructed HIV-1 clade B clones with consensus sequences for gag and/or pol and evaluated the infectivity of viral variants harboring well-defined cytotoxic T-lymphocyte (CTL) escape mutations or drug resistance mutations within this backbone or the clonal NL4-3 strain. Viral variants with consensus sequences were replication-competent in vitro, although at lower rates than the NL4-3 virus. Introduction of the dominant CTL escape mutation R264K into the newly constructed viruses or into NL4-3 led to a dramatic reduction in infection rates. In contrast to the NL4-3 backbone, the combination of R264K with its compensatory mutation S173A on the consensus backbone led to higher infection rates as compared to the same virus in the absence of R264K and S173A. Furthermore, 2 out of 10 drug resistance mutations in pol led to opposing effects, with an increase in infection rates on the consensus gag/pol backbone and a reduction on NL4-3. Therefore, the effect of the respective viral backbone on infectivity observed in vitro might constitute an additional factor to explain differential kinetics of mutational evasion from immune and pharmaceutical pressure.